RELEVANSI PRINSIP PENGEMBANGAN KURIKULUM PAI DALAM MENJAWAB TANTANGAN PENDIDIKAN KONTEMPORER: STUDI LITERATUR - Adrian Maulana Maulana; Muna Waroh; Dian Oktaviani; Eko Nursalim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the relevance of Islamic Education (PAI) curriculum development principles in addressing contemporary educational challenges. The rapid advancement of digital technology, changes in student characteristics, moral issues, and the demands of 21st-century skills require the PAI curriculum to be more adaptive and contextual. This research employs a qualitative approach using a library research method, with data sources derived from scholarly articles, books, and relevant academic documents. Data analysis is conducted through content analysis, including data reduction, data presentation, and critical conclusion drawing. The findings indicate that curriculum development principles such as relevance, flexibility, effectiveness, continuity, integration, and democratic values play a strategic role in responding to contemporary educational challenges. These principles enable the PAI curriculum to become more contextual, adaptive to technological developments, and capable of integrating Islamic values with modern life demands. However, implementation in practice still faces several challenges, including limited teacher competence, lack of innovative teaching strategies, and the dominance of cognitive-oriented approaches. Strengthening curriculum implementation is necessary through improving teacher competence, developing innovative learning strategies, and integrating values and technology in a balanced manner